Abbreviated and Standard Breast MRI in Neoadjuvant Chemotherapy Response Evaluation: A Comparative Study - Yirgin, Inci K.; Engin, Gulgun; Yildiz, Ş eyma; Aydin, Esra Cureoglu; Karanlik, Hasan; Cabioglu, Neslihan; Tukenmez, Mustafa; Emiroglu, Selman; Onder, Semen; Yildiz, Sevda Ozel; Yavuz, Ekrem; Saip, Pınar; et al. (Current Medical Imaging, 2022)
Objectives: This study aims to investigate the efficacy of abbreviated breast magnetic resonance imaging (MRI) in neoadjuvant chemotherapy (NAC) response evaluation. Methods: MR images of 50 locally advanced breast cancer patients who underwent standard protocol (SP) breast MRI before and after NAC were re-evaluated retrospectively. Abbreviated protocol (AP) was obtained by extracting images from SP and then evaluating them in a separate session. Protocols were compared with the histological findings after surgery as the reference standard. Results: A statistically significant difference was found between the two protocols in response evaluation by the McNemar test (p=0.018). However, the Kappa value was 0.62 (p<0.001), which indicates substantial agreement. No statistically significant differences were found between the two protocols (AP and SP) and pathological results in the McNemar test (p=0.12, p=0.60, respectively). Kappa values were 0.48 (p<0.001) and 0.60 (p<0.001), respectively, which indicates moderate agreement for both protocols with higher values by SP evaluation. The residual maximum median diameters were smaller than the pathology, with both protocols (p<0.001). Conclusion: Despite the statistical differences, there was a significant correlation in response evaluation between the two protocols. The pathological results were moderately correlated with both protocols, with SP slightly higher. However, the residual maximum median diameters were smaller than the pathology with both protocols. These results may limit the use of AP in evaluating the local extent of the tumor, especially in patients who will undergo breast-conserving surgery.
Keywords: radiology